The religious institutions in the contemporaneous normative transformation of sexuality in Chile - Palma, Irma (Revista de Psicología, 2008)
This paper analyzes the relation between religious institutions normative orientations and the sexual practices of subjects, more precisely the effects of the adscription and observance in the context of the transformation of religion as well as the sexuality in the contemporary Chilean society. It analyzes the National Survey on Sexual Comportment, that was done in the year 1998 by the National Commission on HIV/AIDS, CONASIDA, with the collaboration of the Agence Nationale de Researches sur le SIDA, ANRS, France, with people that were born between 1929 and 1978 (N=5407). The analysis shows the effects on gender produced by observance, more intense on women differentiated by individualization logics, among the catholic, and of communitarian subjectivity, among evangelical women; it also shows the generational transformations of secularization and the progressive reduction of the effects of religious institutions on the subjects practices.